Societal views on orphan drugs: cross sectional survey of Norwegians aged 40 to 67 - Desser, Arna S (BMJ Publishing Group Ltd., 2010)
Objective To determine whether a general societal preference for prioritising treatment of rare diseases over common ones exists and could provide a justification for accepting higher cost effectiveness thresholds for orphan drugs. Design Cross sectional survey using a web based questionnaire. Setting Norway. Participants Random sample of 1547 Norwegians aged 40-67. Main outcome measure Choice between funding treatment for a rare disease versus a common disease and how funds should be allocated if it were not possible to treat all patients, for each of two scenarios: identical treatment costs per patient and higher costs for the rare disease. Respondents rated five statements concerning attitudes to equity on a five point Likert scale (5=completely agree). Results For the equal cost scenario, 11.2% (9.6% to 12.8%) of respondents favoured treating the rare disease, 24.9% (21.7% to 26.0%) the common disease, and 64.9% (62.6% to 67.3%) were indifferent. When the rare disease was four times more costly to treat, the results were, respectively, 7.4% (6.1% to 8.7%), 45.3% (42.8% to 47.8%), and 47.3% (44.8% to 49.8%). Rankings for attitude on a Likert scale indicated strong support for the statements “rare disease patients should have the right to treatment even if more expensive” (mean score 4.5, SD 0.86) and “resources should be used to provide the greatest possible health benefits” (3.9, 1.23). Conclusions Despite strong general support for statements expressing a desire for equal treatment rights for patients with rare diseases, there was little evidence that a societal preference for rarity exists if treatment of patients with rare diseases is at the expense of treatment of those with common diseases.